Measuring and Explaining X-Efficiency in the Saudi Banking Sector: Evidence from Data Envelopment Analysis - Abdullah, Bandar M (International Journal of Economics and Financial Issues, 2026)
Today’s financial landscape is characterized by increased volatility and heightened risk; assessing the efficiency of banking institutions is both complex and essential. Globally, banks have undergone profound changes driven by regulatory reforms, financial innovation, risk management, and the increasing digitalization of services, which has increased competition within the sector. In this context, this study aims to analyze the relationship between x-efficiency and selected financial and structural characteristics of Saudi commercial banks, including the size of institutions, profitability as measured by return on assets (ROA), and the volumes of deposits and loans. The empirical analysis is based on a panel of ten banks covering the period 2015–2024. Methodologically, technical efficiency is estimated using the Data Envelopment Analysis (DEA) method, based on linear programming, enabling the evaluation of banks’ relative resource use. The results show that Saudi commercial banks have an average efficiency of 86%, reflecting an overall satisfactory performance of the Saudi banking sector. However, institutions with a score below this threshold are considered inefficient, reflecting suboptimal use of their internal resources. These results underline the importance of adopting more effective management strategies to strengthen the overall performance and competitiveness of banking institutions in a constantly changing financial environment.